2022
DOI: 10.1186/s12912-022-00987-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture in Palestine: university hospital nurses’ perspectives

Abstract: Background Understanding the perspectives of healthcare workers toward patient safety-related activities is critical in maintaining a healthy safety climate. The objectives of this research are 1) to examine the perception of Patient Safety Culture (PSC) at a university hospital in Palestine, and to highlight areas in need of improvement, and 2) to assess the relationship between the outcome dimensions (frequency of events reported, and overall perceptions of safety) and the other dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
(39 reference statements)
3
8
0
Order By: Relevance
“…The study further revealed that good and open communication, as well as the use of various communication methods, including the adoption of WhatsApp social network applications enabled flexible communication within teams. This finding is consistent with a Palestinian study which postulated that the dimension of communication openness was a predictor of the overall perceptions of safety [ 30 ]. This is an indication of a promising development of patient safety culture in the study regions, although there are numerous areas that require improvement.…”
Section: Discussionsupporting
confidence: 92%
“…The study further revealed that good and open communication, as well as the use of various communication methods, including the adoption of WhatsApp social network applications enabled flexible communication within teams. This finding is consistent with a Palestinian study which postulated that the dimension of communication openness was a predictor of the overall perceptions of safety [ 30 ]. This is an indication of a promising development of patient safety culture in the study regions, although there are numerous areas that require improvement.…”
Section: Discussionsupporting
confidence: 92%
“…As regards working hours per week, nearly tow-third were worked more than 36 hours per week, similarly, Zabin, et al (39) , found that majority of the participants worked about 40 to 69 h a week, while almost a third of them worked about 20 to 29hrs a week. Additionally, Teleş & Kaya (40) found that the participants had 6 years of professional experience and worked for 60hrs or more per week, this indicates the shortage of nurses as a global and or may be increased demands of nurses services as a response to increasing populations and number of hospitals.…”
Section: Discussionmentioning
confidence: 82%
“…Using different study designs, such as qualitative research and a variety of data collection methods, could help improve understanding of the safety culture and health care provider perceptions and would be required to address the existing relationship between safety culture and nursing competency (Alqattan et al, 2019) Measurement of safety nursing competency Eight of the studies, or 50% of the literature, in this review showed that nurses were more competent in communicating effectively than working in teams with colleagues, and their overall safety culture score was positive. Likewise, Zabin et al (2022) found that both organizational learning and continuous improvement, as well as cooperation within units, received the highest composite frequency of patient safety perception.…”
Section: Measurement Of Patient Safety Culturementioning
confidence: 94%